The role of mentorship in minimally invasive surgery simulation training - Percul Carolina; Prodan Silvana; Vagni Roberto; Busaniche Julio; Lobos Pablo; Moldes Juan; Elmo Gaston (Elsevier, 2024)
ABSTRACT: Background: Surgeons and surgical trainees are expected to be highly skilled in minimally invasive surgical techniques. Simulation allows unlimited practice and repetition without jeopardizing patient safety. This study aimed to analyze the impact of simulation and the role of mentorship. Methods: This was a randomized prospective study. Twenty medical students were randomly assigned to one of two groups: independent training or supervised mentoring by a qualified surgeon. Task performance was assessed before and after training. Speed and the GOALS (Global Operative Assessment of Laparoscopic Skills) scale were used to evaluate each subject's performance and to compare groups. Results: At the initial evaluation, only 9 (45%) students were able to complete all the exercises with a mean GOALS score of 2.54. In contrast, at the end of the training, all students were able to complete all exercises (p=0.004) with a 4.17 mean score (p=0.002). Duration of the exercises decreased by an average of 45% with a mean duration of 286.14 seconds per exercise before and 186.57 (range 28-330) after training (p=0.01). Students in the mentored group achieved higher scores in all exercises than those not mentored (average of 4.34 vs 3.99). Conclusions: This study in medical students without previous surgical experience reinforces the value of simulation-based training. Mentorship has proven to have a positive impact on the ability to acquire surgical skills. The application of mentored simulation strategies could be of valuable use if incorporated into surgical training programs.